2021
DOI: 10.3390/e23081057
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Offline Functional Model Carrying Aging-Specific Growth Rate Information and Recombinant Protein Expression: Entropic Extension of Akaike Information Criterion

Abstract: This study presents a mathematical model of recombinant protein expression, including its development, selection, and fitting results based on seventy fed-batch cultivation experiments from two independent biopharmaceutical sites. To resolve the overfitting feature of the Akaike information criterion, we proposed an entropic extension, which behaves asymptotically like the classical criteria. Estimation of recombinant protein concentration was performed with pseudo-global optimization processes while processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“… where x is the biomass concentration (g kg −1 ), t is the time (h), OUR is the oxygen uptake rate (g kg −1 h −1 ), and (g g −1 ) and β (g g −1 h −1 ) are the stoichiometry parameters that determine the growth and maintenance properties of biomass. The SGR estimation procedure suggested in this study originates from biomass concentration estimates that were based on a bioreactor exhaust gas analysis [41] , [28] . The chosen method exhibited stability in estimating biomass concentrations at various cultivation conditions.…”
Section: Methodsmentioning
confidence: 99%
“… where x is the biomass concentration (g kg −1 ), t is the time (h), OUR is the oxygen uptake rate (g kg −1 h −1 ), and (g g −1 ) and β (g g −1 h −1 ) are the stoichiometry parameters that determine the growth and maintenance properties of biomass. The SGR estimation procedure suggested in this study originates from biomass concentration estimates that were based on a bioreactor exhaust gas analysis [41] , [28] . The chosen method exhibited stability in estimating biomass concentrations at various cultivation conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Such an assumption suggests that these parameters are influenced not only by the immediate state of the cells but also the average age of the individual cells which are present. The latent average age points to the active biomass concentration within the population [37,38]:…”
Section: Latent Parametersmentioning
confidence: 99%
“…Previous studies showed that specific growth rate µ is one of the best descriptors for estimating bioprocess parameters [10]. This parameter and oxygen uptake rate (OUR) carry much information about the growth and life of the cell [11,12].…”
Section: Input Selectionmentioning
confidence: 99%
“…Substrate consumption and broth weight give model information about biomass growth, and broth weight also gives information about the dilution effect of substrate feeding. Additionally, broth and consumed substrate weight with supplementary aging-related information are separate inputs introducing the cumulative regularization [10]. The selected inputs were (Table 1):…”
Section: Input Selectionmentioning
confidence: 99%